Surveying Preschoolers’ Computer Use Capabilities - Vitoulis, Michael (International Journal of Computer (IJC), 2017)
This study detected computer skills that children have developed spontaneously in their everyday lives and those that have already possessed during their studies at the early childhood education centers. The survey involved 453 children, aged 3 to 5, attending 24 different early childhood education structures. A 25-point computer skill observation form, supported by a corresponding rubric, was used to describe the computer capabilities of preschool children. According to the results of the study, as children registered for early childhood education settings, they brought with them their pre-existing computer skills. These skills could potentially hold a key role in designing future educational programs. The age of children seemed to affect these skills up to the age of 4. Implications of findings, concerning computer skills of preschool children, are discussed.